2017
DOI: 10.1186/s11671-017-2078-9
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Dual-Modality Imaging System for Quantitative Detection of Color or Fluorescent Lateral Flow Immunochromatographic Strips

Abstract: Nowadays, lateral flow immunochromatographic assays are increasingly popular as a diagnostic tool for point-of-care (POC) test based on their simplicity, specificity, and sensitivity. Hence, quantitative detection and pluralistic popular application are urgently needed in medical examination. In this study, a smartphone-based dual-modality imaging system was developed for quantitative detection of color or fluorescent lateral flow test strips, which can be operated anywhere at any time. In this system, the whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The visual detection limit of the LFIAs is 10 ng/g. Additionally, we employed a portable smartphone strip reader with multiple image processing to analyse strips in 3 s [19,21]. The LOD is 0.3 ng/g.…”
Section: Comparison Between Hplc and Immunochromatographic Strip For mentioning
confidence: 99%
See 1 more Smart Citation
“…The visual detection limit of the LFIAs is 10 ng/g. Additionally, we employed a portable smartphone strip reader with multiple image processing to analyse strips in 3 s [19,21]. The LOD is 0.3 ng/g.…”
Section: Comparison Between Hplc and Immunochromatographic Strip For mentioning
confidence: 99%
“…A fluorescence detection apparatus that was coupled to a desktop computer or laptop, enabling rapid processing speeds and stable performances, recorded the fluorescence intensity of the dot. However, these bulky and heavy devices limit their widespread application in the field of family and personal care [19][20][21]. Alternatively, a mobile device-based strip reader could satisfy the requirement of high portability and feature-rich testing.…”
mentioning
confidence: 99%
“…Recently, smartphone-based dual-modality imaging system [45] was developed by us, which could quantitativly detect color or fluorescent lateral flow test strips and be operated anywhere at any time, Fig. 9.…”
Section: Research On the Detection Systemmentioning
confidence: 99%
“…Ling et al reported a lateral flow-through strip for use with a smartphone camera that could quantitatively detect alkaline phosphatase activity in milk [31]. Hou et al developed a smartphone-based, dual-modality imaging system that quantitatively detected either color or fluorescent LFIS [32]. In previous reports, smartphone-based LFIS readers were used directly with smartphone cameras to capture images of the LFIS test results.…”
Section: Introductionmentioning
confidence: 99%